The Relationship Between Learning Motivation and Learning Activity of Office Application Program Training Participants at LKP Smart College Padang City - Sekar Wangi, Annisa; Natsir, MHD (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research was motivated by the lack of active learning of training participants in the learning process. It is suspected that there is inclusive learning motivation among training participants. This research aims to: 1) describe the learning motivation of trainees, 2) describe the learning activeness of trainees in the learning process, 3) see the relationship between learning motivation and the learning activeness of training participants in the office application program at LKP Smart College Padang City. This research uses a quantitative approach with a correlational type. The population of this study was 39 training participants at LKP Smart College and a sample of 75%, namely 29 people, used the cluster random sampling technique. Data collection methods use questionnaires or questionnaires. The research findings show that: (1) the learning motivation of trainees in the learning process is in the low category. (2) the learning activeness of trainees in the learning process is low. (3) there is a significant relationship between learning motivation and the learning activeness of participants in the office application training program at LKP Smart College Padang City.